Determination of residual strain in steel wire cord by chemical method - N. A. Zmeeva (Литьë и металлургия, 2019)
The article presents a method for determining the residual strain in the steel wire cord of construction 3x0,30. The causes of residual strain, the effect on the quality of finished product and the determination of the degree of residual strain by chemical method are considered. The cause of residual strain is uneven plastic deformation of a solid body due to various changes in different places of its length and volume. Residual strain of steel wire cord are made up of stresses existing in the wire after drawing, and the stresses created during the lay of wire.An important task in the framework of the metal wire cord manufacturing technology, which is faced by specialists at «BMW» – the Management Company of the Holding «BMC» is to reduce residual strains at all stages of metal wire cord manufacturing. Residual strains are an additional factor affecting the adhesive strength and durability of adhesive joints.The principle of determining the residual strains is to remove the coating from the metal wire cord, paint the transverse halves of each thread. Then the filaments are impregnated with nitric acid, and the residual strain on the surface is recorded as the difference between the residual strains of the two halves of the wire.